PKM Pendampingan Pembuatan HIDING (Hiasan Dinding dari Stik Es Krim) - Sri Utami; Nurjannah Nurjannah; Sitti Hajerah Hasyim; Mustari Mustari; Nur Arisah (Lembaga Pengembangan Kinerja Dosen, 2025)
Wall Decorations from Ice Cream Sticks (HIDING) are a craft innovation in the decorative wall art industry. As we know, wall decorations are widely used to enhance aesthetics, beautify, and create a pleasant atmosphere in homes. They are commonly displayed in bedrooms, living rooms, dining areas (kitchens), and are also often found in workspaces, meeting rooms, art galleries, and cafés. The innovation of creating wall decorations from ice cream sticks aims to develop creative works from recycled materials, turning them into products that are equally attractive compared to those made from wood, plastic, or metal. These products offer aesthetic, artistic, and creative value that can attract public interest.The methods used in this program include lectures, discussions, and hands-on training. The results of the activity include: (1) The HIDING training was well received by the participants; (2) The high interest and motivation of the participants supported effective knowledge and skills transfer from facilitators to trainees, ensuring full absorption of the materials; and (3) The HIDING products have the potential to be developed into entrepreneurial products.